In Situ Chemical Reduction of CVOC and Chromium Facilitated Redevelopment of an Industrial Property - Mueller, Jim; Gray Mike McKim, Doug; McKim, Mike; Shinkawa, Taki; Bishop, Elizabeth; Meese, Wade (Águas Subterrâneas, 2013)
Safe implementation of efficient and cost-effective remedial solutions in the clean-up of impacted properties is paramount in returning brownfields and other impacted properties to viable use in the face of the recent real estate market declines. As part of the overall project area remediation effort, sustainable and innovative in situ remedial technologies were evaluated for use per proposed site redevelopment plans for the portion of the site formerly utilized for plating operations. The successful design, implementation of the in situ remedy and performance monitoring of the targeted treatment area resulted in the attainment of required clean-up standards and no further action within nine months of the remedy implementation.